Pengembangan Media Pembelajaran Google Sites Materi Sholat Sunnah Kelas VIII SMP Islam Brawijaya - Shafira Dwi Apriliani; Hidayatur Rohmah; Nur Khafidhoh; Ulfa Wulan Agustina; Chusnul Chotimah (JoEMS (Journal of Education and Management Studies), 2026)
Purpose: This research aims to develop and validate interactive learning media based on Google Sites for teaching Sunnah Prayers (Sholat Sunnah) to eighth-grade students. Methodology/Approach: The development follows the systematic stages of the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model, with validation limited to expert assessment by 2 media experts and 2 Islamic Religious Education material experts. The validity and feasibility of the media were tested through structured expert evaluation using a 5-point Likert scale. Findings: The validation results from media experts showed a score of 86% (Feasible category), while the assessment from material experts obtained 98% (Very Feasible category). The developed media successfully integrates multimedia elements including text, images, videos, and interactive quizzes that are easily accessible to students. Practical Implications: The learning media is declared feasible for use in PAI instruction. However, classroom implementation stages have not yet been conducted; evaluation consists of revisions based on expert feedback. Originality/Value: This digital innovation offers a specific and structured solution for teaching Sunnah Prayers to Grade VIII students, potentially improving student motivation, understanding, and learning independence in Islamic Religious Education while addressing modern educational challenges.